Self-Regulation and Shame as Mediators Between Childhood Experiences and Young Adult Health - Rollins, Elizabeth Mathews; Crandall, AliceAnn (Frontiers in Psychiatry, 2021)
The purpose of this study was to determine whether self-regulation and shame mediated the relationship between adverse and positive childhood experiences (ACEs and PCEs) and young adult health. Data came from the Flourishing Families Project (FFP), a 10-year longitudinal study. Adolescent participants (N = 489; 51% female) completed an annual survey. Data were analyzed using structural equation modeling. Results indicated that PCEs negatively predicted shame and positively predicted self-regulation while ACEs negatively predicted self-regulation. Shame mediated the relationship between PCEs and depression. Self-regulation mediated the relationship between both ACEs and PCEs with anxiety; self-regulation also mediated the relationship between ACEs and substance abuse. Childhood experiences appear to affect the development and maintenance of self-regulation in adolescence. Self-regulation appears to be especially important in protecting against depression, anxiety, and substance abuse in young adulthood.